BOARD OF COMMISSIONERS AGE DIVERSITY, PROFITABILITY, AND BANK RISK-TAKING - Setiawan, Rahmat; Lumumba, Ahmad Wisesa; Herlinawati (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: The age of the board of commissioners is one of the personal characteristics of commissioners that can affect the level of bank profitability and risk-taking. This study examines the effect of the board of commissioners' age diversity on bank profitability and risk-taking. Methods: The author uses the multiple linear regression method using a total of 223 observations in banking companies listed on the Indonesia Stock Exchange for the period 2008-2017. Results: The dependent variables used in this study are Return on Assets (ROA), Return on Equity (ROE), and bank risk investment, with the independent variable being the age diversity of the board of commissioners. The results of this study indicate that the age diversity of the board of commissioners has a significant negative effect on the level of bank profitability, as measured by ROA and ROE. However, the age diversity of the board of commissioners has a significant positive effect on bank risk-taking. Conclusion and suggestion: The selection of the Board of Commissioners needs to pay attention to the ages of the members of the Board of Commissioners as a whole because the results of this study indicate that high age diversity in the scope of commissioners can worsen bank profitability and higher risk-taking.